Alfamart's Image Repair Strategies on Chocolate Theft Incident in the News of detik.com and kompas.com - Sabila, Mayta; Purworini, Dian (Universitas Muhammadiyah Surakarta, 2022)
Purpose: This study aims to identify how Alfamart’s image repair strategy is applied to the crisis that is published in Detik.com and Kompas.com. Methodology: This study applies a descriptive quantitative approach with content analysis techniques. The population in this research is all the news in Detik.com and Kompas.com related to the crisis experienced by Alfamart. The sample is determined by purposive sampling, and the data analysis was carried out with an independent t-test. Results: The results of the study mention that there is no significant difference between the two online media in reporting the Alfamart case. Alfamart has repair its image through corrective action, denial, bolstering, good intentions, and compensation. Applications/Originality/Value: This study seeks to compare the coverage in online media regarding the Alfamart case controversy. The differences in this study include research objects, measuring instrument, literature, theory, and research results.